Implementasi Kebijakan Pendistribusian Liquified Petroleum Gas (LPG) 3 Kilogram di Kecamatan Palu Barat Kota Palu - Juli Apryani; Mashuri H. Tahili; Subhan Haris (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the implementation of the Liquefied Petroleum Gas (LPG) 3-kilogram distribution policy in West Palu District, Palu City, using the Van Meter and Van Horn policy implementation model. The analysis focuses on six variables: policy standards and objectives, resources, inter-organizational communication, characteristics of implementing organizations, implementer disposition, and social, economic, and political conditions. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings indicate that the implementation of the LPG 3-kilogram distribution policy in West Palu District has not been optimal. In terms of policy standards and objectives, the distribution remains poorly targeted, as subsidized LPG is more frequently accessed by middle- to upper-income households and retailers rather than low-income households. Resource-related constraints include limited personnel, weak supervision, and inconsistent application of safety equipment and quality control procedures. Inter-organizational communication is also inadequate, reflected in insufficient socialization and data inconsistencies within the Merchant Apps Pertamina (MAP), resulting in non–real-time recording of quotas and stock levels. Furthermore, many LPG bases do not fully comply with standard operating procedures, such as cylinder inspections and document verification, while variations in implementer compliance persist, including sales above the regulated price ceiling. Low public awareness regarding the intended beneficiaries of LPG 3 kilograms further exacerbates mistargeting. The study concludes that these issues are systemic and interconnected. Strengthening supervision, enforcing sanctions, improving digital data synchronization, enhancing implementer capacity, and intensifying public outreach are essential to ensure that LPG 3-kilogram subsidies reach their intended beneficiaries.